Transgenic Overexpression of 14-3-3 Zeta Protects Hippocampus against Endoplasmic Reticulum Stress and Status Epilepticus In Vivo - Brennan, Gary P. (Public Library of Science, 2013)

(untitled)
14-3-3 proteins are ubiquitous molecular chaperones that are abundantly expressed in the brain where they regulate cell functions including metabolism, the cell cycle and apoptosis. Brain levels of several 14-3-3 isoforms are altered in diseases of the nervous system, including epilepsy. The 14-3-3 zeta (ζ) isoform has been linked to endoplasmic reticulum (ER) function in neurons, with reduced levels provoking ER stress and increasing vulnerability to excitotoxic injury. Here we report that transgenic overexpression of 14-3-3ζ in mice results in selective changes to the unfolded protein response pathway in the hippocampus, including down-regulation of glucose-regulated proteins 78 and 94, activating transcription factors 4 and 6, and Xbp1 splicing. No differences were found between wild-type mice and transgenic mice for levels of other 14-3-3 isoforms or various other 14-3-3 binding proteins. 14-3-3ζ overexpressing mice were potently protected against cell death caused by intracerebroventricular injection of the ER stressor tunicamycin. 14-3-3ζ overexpressing mice were also potently protected against neuronal death caused by prolonged seizures. These studies demonstrate that increased 14-3-3ζ levels protect against ER stress and seizure-damage despite down-regulation of the unfolded protein response. Delivery of 14-3-3ζ may protect against pathologic changes resulting from prolonged or repeated seizures or where injuries provoke ER stress.